0934 Effects of Sleep Quality and Pain Intensity on Negative Affect in Idiopathic Parkinson's Disease. (12th April 2019) - Crew, Earl C; Price, Catherine E; Robinson, Michael E
Abstract: Introduction: Parkinson's disease (PD) is clinically characterized by chronic, progressive impairments in motor and non-motor functioning. The non-motor symptoms (NMSs) of PD include mood disturbances, sleep difficulties, and chronic pain. Dopaminergic cell loss plays a large role in explaining the prevalence of affective disorders in PD, as symptoms of anxiety and depression are highly responsive to antiparkinsonian medications. However, mood difficulties often persist in PD patients on dopamine therapy, suggesting other contributing factors aside from neurodegeneration. This study examined whether other NMSs of PD, specifically sleep and pain, may contribute to negative affect among patients with PD. Methods: 20 patients with idiopathic PD (age=67.8±6.1) and 19 age-matched controls (age=69.7±6.5) completed bi-daily (morning and evening) surveys for 14 days to collect average ratings of their nightly sleep quality (SQR; 1=Very Poor Sleep; 5=Very Good Sleep), daily pain intensity (0-100 Visual Analog Scale, 100=Worst Pain Sensation Imaginable), and daily negative affect (NA; measured by the PANAS-SF; 1=never, 5=always; range= 5-25). PD-related variables including motor symptom severity (UPDRS Part III) and intensity of antiparkinsonian medication (levodopa-equivalent dosage or LED) were also collected. Hierarchical regression was performed predicting NA scores (higher=more NA) with the following steps: Step 1: UPDRS Part III, LED; Step 2: SQR; Step 3: Pain Intensity. Results: The model showed that NA ratings were related to our PD variables (Step 1: R 2 =.232), while adding SQR in Step 2 ( R 2 =.317) improved model fit and uniquely predicted NA (β= -0.335). In the final Step 3 model ( R 2 =.600, p <.001), SQR (β= -0.317) and pain intensity (β= 0.589) were both uniquely associated with NA after adjusting for other PD-related variables. Conclusion: Poorer subjective sleep quality and higher self-reported pain were associated with negative affect independent of motor symptom severity or intensity of antiparkinsonian medication in patients with PD. The symptoms underlying poorer sleep quality and higher pain intensity in PD patients warrants further study. Modifiable aspects of sleep and pain in PD could be targeted in intervention studies to improve patient outcomes. Support (If Any): NINDS K23NS060660 and R01NS082386 (Price).